Evaluation of beef characteristics of Ayrshire bulls based on progeny groups - Ruohomäki, Hilkka; Varo, Mikko (Agricultural and Food Science, 1969)
Progeny groups with an average of 8 bull calves from nine Ayrshire bulls were raised on uniform feeding where concentrates were fed ad lib., to an age of 6 months. The carcasses were evaluated, and their right half was cut. In order to estimate the between-sire variance and the heritability values, analyses of variance were performed. The between-sire variances were statistically significant for live weights and carcass weights and thus also for the weights of carcass half. The between-sire variance for results in kilograms was generally statistically significant, but for proportions in per cent the values were significant only in a few instances. The differences between sires were statistically highly significant for the relative proportions of fore and hind parts, which presumably is due to the sires being of different body conformation. The between-sire variance with regard to the amount of meat in kilogram is statistically significant for almost all parts of the carcass, but – except for the round – the differences with regard to meatiness percentage are slight. The amounts of meat obtained from different parts of the carcass, expressed as proportions of the total amount of meat, varies statistically significantly in most cases, which also points to the differences in body conformation of the animals. The area of the musculus longissimus dorsi was neither correlated with the weight of the carcass nor with the meatiness percentage. There was no difference between the sires with regard to the carcass grading except the round and shoulder. The grades for meatiness gave no clue to the meat percentage of the carcass or to the carcass weight or to the actual amount of meat, although earlier studies have shown grades of meatiness to follow the two latter characteristics. It may be pointed out that the present study is a preliminary one and will be completed with further trials.